Najmuddīn Al-Tūfī's Thoughts on The Dynamics of Inheritance Law 2:1 Perspective of Maṣlaḥah - Rahmad Setyawan; Muhaman Taufik Kustiawan (State Islamic University (UIN) of Sunan Ampel, 2021)
Islamic hereditary law in the reality of human life demands legal dynamism to vouch for the flexibility and adaptability of genetic law following the characteristics of modern Muslim societies. This article elaborates on the dynamics of the 2: 1 inheritance law between heirs, male and women, from the perspective of the maṣlaḥah of Najmuddīn al-Ṭūfī. To analyze the conception of inheritance 2:1 division, this study attempts to dissect it with the theory of maṣlaḥah Najmuddīn al-Ṭūfī. The studies and analysis have been discovered, resulting in the conclusion that the dynamics of the 2: 1 hereditary law has been subject to embodying the benefits properly. In the view of Najmuddīn al-Ṭūfī, the help is the goal of sharia, even the highest argument if it is contradicted between text and maṣlaḥah. This view, when applied to the verse of the Holy Qur'an, An Nisa (4): 11, will open up opportunities for responsive reinterpretation. Based on this concept, it is understood that deviating from the law of text in the distribution of inheritance is permissible to create benefits for the heirs and avoid disputes.